2023
DOI: 10.1002/adfm.202301268
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Detection of SARS‐CoV‑2 by Flexible Metal Oxide Field‐Effect Transistors

Sihui Hou,
Mengge Wu,
Hu Li
et al.

Abstract: The pandemic of coronavirus disease 2019 (COVID‐19) reflects the great significance of rapid and accurate detection of pathogens by new sensing technologies. Antibody based biosensors with high sensitivity comparable to golden standard polymerase chain reaction (PCR) and miniaturized device features allow the detection of pathogens in portable and flexible formats. Herein, flexible metal oxide electrolyte‐gated field‐effect transistors (EGFETs) are reported to serve as the biosensors for rapid and ultrasensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…[9,10] Additionally, as an anisotropic material, 𝛽-Ga 2 O 3 can sustain phonon polaritons along different directions over a wide spectral range according to theoretical predictions, [6,34] which is desirable for nanophotonic applications. Thanks to the recent development of electron energy loss spectroscopy (EELS) with support from scanning transmission electron microscopy (STEM), an electron probe with atomic spatial resolution and a sub-10 meV energy resolution, as well as an extremely wide spectral range (from ≈20 meV to 3 keV) can be achieved, [35][36][37][38][39][40][41] making it possible to study the HShP modes of 𝛽-Ga 2 O 3 in a diversity of nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Additionally, as an anisotropic material, 𝛽-Ga 2 O 3 can sustain phonon polaritons along different directions over a wide spectral range according to theoretical predictions, [6,34] which is desirable for nanophotonic applications. Thanks to the recent development of electron energy loss spectroscopy (EELS) with support from scanning transmission electron microscopy (STEM), an electron probe with atomic spatial resolution and a sub-10 meV energy resolution, as well as an extremely wide spectral range (from ≈20 meV to 3 keV) can be achieved, [35][36][37][38][39][40][41] making it possible to study the HShP modes of 𝛽-Ga 2 O 3 in a diversity of nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…These "absolute value signals" directly collect and process the specific changes in biomolecules. Although these signals carry the biomolecules' charge information [8][9][10], they have the drawbacks of incomplete, unstable, and unreliable detection. Kulkarni et al reported that the detection range of FET-based biosensors was limited by the Debye length due to the Debye screening effect.…”
Section: Introductionmentioning
confidence: 99%